2019
DOI: 10.1186/s12967-019-2129-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying genetic variants underlying medication-induced osteonecrosis of the jaw in cancer and osteoporosis: a case control study

Abstract: BackgroundBisphosphonate-induced osteonecrosis of the jaw (BRONJ) presents with a typical pattern of jaw necrosis in patients who have been prescribed bisphosphonates (BPs) and other antiangiogenetic drugs to treat osteoporosis or bone-related complications of cancer.MethodsThis study divided 38 patients with BRONJ into two groups according to the prescribing causes: cancer (n = 13) and osteoporosis (n = 25), and underwent whole exome sequencing and compared them with normal controls (n = 90). To identify cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Thus, the establishment of an in silico method can be important and beneficial to the field, which enable us to narrow down and focus on those potentially critical gene-drug combinations. Ab initio GVB may be applied to discover unknown pharmacogenes with significant inter-individual drug response variabilities [6][7][8]. Further improvements and molecular validations should be required before use GVB as a supportive tool for drug safety scoring for a given drug for an individual or population, using NGS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the establishment of an in silico method can be important and beneficial to the field, which enable us to narrow down and focus on those potentially critical gene-drug combinations. Ab initio GVB may be applied to discover unknown pharmacogenes with significant inter-individual drug response variabilities [6][7][8]. Further improvements and molecular validations should be required before use GVB as a supportive tool for drug safety scoring for a given drug for an individual or population, using NGS.…”
Section: Discussionmentioning
confidence: 99%
“…This enables alternative approaches for predicting the inter-individual drug response differences. Gene-wise variant burden (GVB), an integrated gene-level measure of the cumulative impact of the multitude of deleterious variants, including common, rare, and even novel variants on a given gene, has been successfully applied to address many pharmacogenetic problems [5][6][7][8]. Pharmacokinetic and pharmacodynamic genes associated with withdrawn, precautionary, and the US FDA-approved pharmacogenomics biomarker drugs exhibited significantly lower GVBs than those associated with safe drugs [5].…”
Section: Introductionmentioning
confidence: 99%
“…40 The expression of TGF-β and angiogenesis-related signalling have been shown to be possible consequences of MRONJ. 41 Altered VEGF expression has been observed following treatment with BPs, 42 possibly related to the expression of TGF-β. 16 Soft tissue toxicity Although osteoclasts and bone are the primary targets following their exposure to BPs, it has been reported that the toxicity of BPs to soft tissue is closely related to MRONJ.…”
Section: Angiogenesismentioning
confidence: 99%
“… 40 The expression of TGF-β and angiogenesis-related signalling have been shown to be possible consequences of MRONJ. 41 Altered VEGF expression has been observed following treatment with BPs, 42 possibly related to the expression of TGF-β. 16 …”
Section: Pathogenesis and Risk Factors Of Mronjmentioning
confidence: 99%
See 1 more Smart Citation